2007
DOI: 10.1111/j.1365-2753.2007.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of using the low back pain guidelines: a qualitative research

Abstract: Despite an overall positive attitude towards LBP guideline implementation, FPs found it hard to come to terms with the conflicting dimensions of LBP patient care. The patient-doctor interaction determined the outcome of the encounter, whether it complied with the guidelines and whether the encounter leads to a healing process or to a vicious circle of unnecessary utilization of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 21 publications
0
48
0
1
Order By: Relevance
“…Twelve studies did not indicate whether data saturation had been reached (54-57, 59, 60, 63, 65, 67-70); 11 studies did not provide explicit details to enable replication of the data analysis (54-58, 60-63, 65, 69) ; seven did not include independent analysis by two or more researchers (54)(55)(56)(57)(60)(61)(62); and eight did not provide supporting quotes linked to the transcript data (55,57,60,62,64,(68)(69)(70). None of the studies reported on dissonant cases; and 16 did not report the strengths and limitations of their studies (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). Nine studies did not provide recommendations for clinical practice based upon their findings (55, 57, 59-63, 69, 70), and 15 did not provide any recommendations for research (54-57, 59-65, 67-70).…”
Section: Methods Qualitymentioning
confidence: 97%
See 2 more Smart Citations
“…Twelve studies did not indicate whether data saturation had been reached (54-57, 59, 60, 63, 65, 67-70); 11 studies did not provide explicit details to enable replication of the data analysis (54-58, 60-63, 65, 69) ; seven did not include independent analysis by two or more researchers (54)(55)(56)(57)(60)(61)(62); and eight did not provide supporting quotes linked to the transcript data (55,57,60,62,64,(68)(69)(70). None of the studies reported on dissonant cases; and 16 did not report the strengths and limitations of their studies (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). Nine studies did not provide recommendations for clinical practice based upon their findings (55, 57, 59-63, 69, 70), and 15 did not provide any recommendations for research (54-57, 59-65, 67-70).…”
Section: Methods Qualitymentioning
confidence: 97%
“…Eleven studies did not include a theoretical framework (54,56,57,58,60,61,63,65,66,69,70); eight did not report whether or not they obtained ethical approval (54, 57, 60-62, 64, 69, 70); 15 did not report whether or not informed consent was obtained (54-66, 69, 70) and 14 did not report the influence of the researcher and whether participants could give opinions Copyright © 2015 Wolters Kluwer Health, Inc. Unauthorized reproduction of the article is prohibited.…”
Section: Methods Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Plus récemment en Israël, il a été identifi é que le manque de connaissances chez les médecins généralistes était une barrière à l'utilisation d'un guide de pratique pour les lombalgies [11]. Les autres barrières identifi ées étaient les attentes des patients, une vision biomédicale de la lombalgie chez les médecins, leurs contraintes de temps et leur surcharge de travail [10]. En Allemagne, les barrières identifi ées chez les généralistes se situaient au niveau des patients et au niveau de leurs confrères.…”
Section: Les Barrières à L'amélioration Des Pratiques Chez Les Prounclassified
“…Examples of such discrepancies are general practitioners' recommendations about physical activity (Rainville et al, 2000), their use of treatment strategies aimed at psychosocial prognostic factors (Jellema et al, 2005), and physiotherapists' management of low back pain (Mikhail, Korner-Bitensky, Rossignol, and Dumas, 2005;Stevenson, Lewis, and Hay, 2006). Knowledge of guidelines related to the assessment and treatment of back pain is increasing, but there is still a need to improve caregivers' skills and behaviors in relation to guidelines (Borkan et al, 2002;Dahan et al, 2007;Overmeer, Boersma, Main, and Linton, 2009).…”
Section: Introductionmentioning
confidence: 96%